2001
DOI: 10.1002/ana.1287
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral nervous system infection, immunity, and inflammation in the nonhuman primate model of lyme borreliosis

Abstract: The relationship between chronic infection, antispirochetal immunity, and inflammation is unknown in Lyme neuroborreliosis. In the nonhuman primate model of Lyme neuroborreliosis, we measured spirochetal density in the nervous system and other tissues by polymerase chain reaction and correlated these values to anti-Borrelia burgdorferi antibody in the serum and cerebrospinal fluid, and to inflammation in tissues. Despite substantial presence of Borrelia burgdorferi, the causative agent of Lyme borreliosis, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…Two to four months after intradermal inoculation by syringe we found N40 DNA by PCR in all the tissues examined in both immunocompetent and immunosuppressed animals [1,4,5,8,14,15]. However, the [8].…”
Section: Infection Of Immunocompetent Hosts With Lyme Disease Borreliasmentioning
confidence: 86%
See 1 more Smart Citation
“…Two to four months after intradermal inoculation by syringe we found N40 DNA by PCR in all the tissues examined in both immunocompetent and immunosuppressed animals [1,4,5,8,14,15]. However, the [8].…”
Section: Infection Of Immunocompetent Hosts With Lyme Disease Borreliasmentioning
confidence: 86%
“…For this we did microscopical examination of H&E-and immunostained tissue sections and measured mRNA and protein by RT-PCR and immuno-dot-blot, respectively [1,4,5,8,[14][15][16]18]. First we studied the presence and severity of inflammation in tissues from immunocompetent and immunosuppressed non-human primates inoculated with the N40 strain of B. burgdorferi [8].…”
Section: Tissue Response To B Burgdorferi Infection In Non-human Primentioning
confidence: 99%
“…Les anomalies électrophysiologiques, témoi-gnant le plus souvent d'une atteinte axonale, régressent fré-quemment parallèlement à l'évolution clinique [6,23]. Une étude récente sur modèle de primates montre que la neuroborréliose est une infection persistante et que la présence de la bactérie est une condition nécessaire mais non suffisante pour générer une inflammation [27]. Une étude sur 103 patients souffrant de lomboradiculalgies a permis de retrouver chez trois d'entre eux la coexistence d'une hernie discale avec une synthèse intrathécale d'anticorps spécifiques de B. burgdorferi, mais les auteurs écartent la possibilité d'une origine infectieuse en raison de l'absence de radiculite aiguë et de réaction cellulaire associée [28].…”
Section: Discussionunclassified
“…Finally, in a model using our closest relative, the nonhuman primate macaque monkey, Pachner and colleagues [71][72][73][74][75] found that neurologic and cardiac disease were associated with persistent infection in these monkeys, and cytokine and gene expression related to persistent B. burgdorferi infection could be demonstrated 13 months after infection. In summary, these animal models provide "credible scientific evidence" for persistent infection in Lyme disease.…”
Section: Animal Modelsmentioning
confidence: 94%
“…We can start with animal models of Lyme disease [67][68][69][70][71][72][73][74][75]. In the mouse, one study found that "persistence of spirochetes within macrophages provides a possible pathogenetic mechanism for chronic or recurring Lyme disease" [67, p. 909].…”
Section: Animal Modelsmentioning
confidence: 99%